"The assessed loss as the driving force behind schemes of arrangement and compromises under s 311 of the Companies Act 61, 1973, as amended" - Maloka, Tumo Charles (Department of Public Law, 2021)
The desire of virtually all taxpayers today is to find some means of minimizing their taxes. The search for tax shelters by taxpayers is relentless. Tax considerations are hallmarks of scheme of arrangements and compromise carried out in terms of s3 11 of the Companies Act. The scheme of arrangements gained popularity during the sanctions era as a tax saving device. Broadly speaking, s311 schemes have been employed as a relatively inexpensive method of acquiring financially distressed company being wound up with one of the most alluring commodities from tax point of view - a large balance of assessed loss to generate tax-sheltered income. The retention of assessed loss is paramount concern of proposers of s 311 scheme of arrangements and compromise with creditors. It is, therefore, a matter of considerable import that an insolvent company's assessed loss remain largely intact. And when it comes to structuring an arrangement or compromise, the choice of scheme is even more crucial especially if the objective is the set-off of assessed loss against current income. The assessed loss has been described as the leit motif behind the beneficial use of statutory corporate re-organization facilitated by s 3 11 of the Companies Act. To the extent that schemes of arrangements and compromise are used to obtain substantial tax savings, the taxpayers make very considerable inroads into the fiscus. As soon as one starts to engage in s3 l l schemes of arrangements and compromise, one is liable to draw bit of attention to trafficking in assessed losses of companies and to provoke the Commissioner of Inland Revenue into a counter-attack. The opportunity to get assessed loss set-off against income is governed by two complimentary provisions, namely, sections 20 and 103(2). Section 20(1) results in a forfeiture or sterilization of assessed where there was mercantile abstinence on the part of the company. While section 20(1)(a)(ii) provides that the balance of assessed loss shall be reduced by the amount or value of any benefit received by or accruing to a person resulting from a concession granted by or compromise made with his creditors whereby his liabilities to them have been extinguished, provided that such liabilities arose in the course of trade. Further disqualification is provided by s103(2) which is specifically aimed at restricting trafficking in assessed losses of companies. The tax efficacy of s311 schemes can be easily overshadowed by adverse tax treatment under aforementioned provisions.